Problems of Business Activity of the Enterprise - T., Akhmedova A. (European Journal of Life Safety and Stability (2660-9630), 2022)
The article reveals the main meaning and problems of the business activity of an enterprise, which, especially in crisis conditions, becomes one of the most important factors in both the efficiency and prospects of individual enterprises of firms and the industry as a whole.